The role of information and communication technology in customer relationship management- a case study of the industrial cement company of skikda - hannache, habiba (Journal of Excellence for Economics and Management Research, 2025)
Thy study aimed to highlight the relationship between information and communication technology and customer relationship management at the industrial cement company of skikda, considering that information technology helps build strong relationships with customers by enhancing interaction ,analyzing data, protecting customer information ,and automating processes, where we addressed the concepts related to both information and communication technology ( the independent variable) and customer relationship management(dependent variable).to address the problem related to information and communication technology in customer relationship management at the company under study .a questionnaire was designed to collect data, which was distributed to 70 individuals .A total of 51 valid forms were retrieved for the study .The responses of the sample members were tested using the sppss 21 software. The study concluded that the company under study relies on using information and communication technology tools and applications, especially communication networks and phones;to manage its relationship with customers. The researcher recommends that the company design a website or a dedicated page to promote its products